The implications of the diving response in altering carbon dioxide sensitivity as measured by changes in heart rate, respiration rate and psychological measures in panic disorder patients - Kyriakoulis, Peter; Caballero, Catherine Lissette (Frontiers in Psychiatry, 2025)
IntroductionBreath-hold divers are known for their exceptional breathing control and reduced carbon dioxide (CO2) sensitivity due to training adaptations. In contrast, individuals with panic disorder (PD) often exhibit heightened CO2 sensitivity. This study aimed to explore the potential clinical applications of the diving response (DR), particularly cold facial immersion (CFI), in mitigating panic-related symptoms and cognitions by modulating CO2 sensitivity.MethodsThis study investigated the effects of the CFI task on individuals with PD and a comparison group. Changes in heart rate, respiration rate, and psychological measures were assessed before and after a CO2 challenge to determine whether the CFI task could reduce CO2 sensitivity and panic-related symptoms.ResultsThe results did not support the efficacy of the CFI task in reducing physiological markers of CO2 sensitivity—specifically, heart rate and respiration rate—following the CO2 challenge in either the clinical or comparison group, potentially due to the small sample size. However, significant reductions in both physiological and cognitive symptoms of panic were observed in the clinical group following the CFI task.DiscussionAs hypothesized, the CFI task demonstrated anxiolytic effects in individuals with PD by reducing self-reported anxiety and panic symptoms. These findings highlight the potential of the CFI task for clinical application in the treatment of panic disorder, warranting further research with larger samples.